Factors predicting the length of stay in inpatient forensic psychiatric care in Hungary - Fekete, Szabolcs; Girasek, Hunor; Ungvari, Gabor S.; Gazdag, Gábor (Frontiers in Psychiatry, 2025)
IntroductionIn recent years, the length of stay (LoS) in forensic psychiatric inpatient institutions has been increasing worldwide. Although an excessive LoS constitutes a human rights violation, the underlying reasons and associated factors have not been fully established, and differences between countries and regions have led to limited conclusive information.MethodsThis retrospective study used data from a nationally representative sample of 301 adult patients who were admitted to the National Institute of Forensic Psychiatry, Hungary’s only forensic inpatient psychiatric institution, following a court-issued compulsory treatment order for reason of insanity during 2000–2015 to investigate the demographic, clinical, and criminal offense-related factors associated with inpatient LoS.ResultsAmong the variables found to be significant in univariate analyses, a multiple regression model with bootstrapping confirmed significant associations of LoS with the type and method of the index criminal offense, community residential setting into which the patient was released, age and gender (all p < 0.05). However, the regression model accounted for only 34.1% of the observed variance in LoS, suggesting the presence of additional unexplored factors that may lead to excessive LoS.ConclusionThe Hungarian forensic psychiatric system should implement a more evidence-based method for determining the LoS for inpatient care.